Codon usage bias in chloroplast genes implicate adaptive evolution of four ginger species - Yang, Qian; Xin, Cheng; Xiao, Qing-Song; Lin, Ya-Ting; Li, Li; Zhao, Jian-Li (Frontiers in Plant Science, 2023)
Codon usage bias (CUB) refers to different codons exhibiting varying frequencies of usage in the genome. Studying CUB is crucial for understanding genome structure, function, and evolutionary processes. Herein, we investigated the codon usage patterns and influencing factors of protein-coding genes in the chloroplast genomes of four sister genera (monophyletic Roscoea and Cautleya and monophyletic Pommereschea and Rhynchanthus) from the Zingiberaceae family with contrasting habitats in southwestern China. Nucleotide composition analysis revealed that the overall G/C content of the coding genes was ˂ 48%, indicating a high abundance of A/T bases. Additionally, synonymous and optimal codons were biased toward ending with A/U bases. Natural selection is the primary factor influencing CUB characteristics, particularly photosynthesis-associated genes. We observed differential gene expressions related to light adaptation among sister genera inhabiting different environments. Certain codons were favored under specific conditions, possibly contributing to gene expression regulation in particular environments. This study provides insights into the adaptive evolution of these sister genera by analyzing CUB and offers theoretical assistance for understanding gene expression and regulation. In addition, the data support the relationship between RNA editing and CUB, and the findings shed light on potential research directions for investigating adaptive evolution.